DISCLOSURE ATAS MANAGEMENT STATEMENT, INTELLECTUAL CAPITAL, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Sri Imaningati; Mekani Vestari (Jurnal Akuntansi Indonesia, 2016)
Value of the firm is an investor perception about the condition of the firm, which is often refered to the stock price. High stock prices indicate high public appreciation of the firm. Efforts to maximize value of the firm is done by maximizing the factors that influence it. This study used three variables, namely Statement Management Disclosure, Intellectual Capital Disclosure, and Corporate Social Responsibility Disclosure. The object of the research ismanufacturing company from 2009 to 2013. Samples were collected by purposive sampling method. Multiple linear regression model used in this research model testing. The results showed that CSR Disclosure had a positive effect on Firm Value. Intellectual Capital Disclosure does not affect the Firm Value, while Management Statement Disclosure had a negative effect on the Firm Value.